Jack Delano papers - Delano, Jack.
Chiefly correspondence, notebooks, and caption books relating to works by Delano as a photographer for the Farm Security Administration and the Office of War Information depicting the Great Depression, railroads in the West, Acadian farmers in Maine, and life in the South and in Puerto Rico and the Virgin Islands. Also includes transcript of an oral history interview conducted with Delano sponsored by the Archives of American Art and material relating to Elizabeth Kenny.
Most photographs in the collection are housed in the Prints and Photographs Division.
Photographer, filmmaker, classical music composer, and book illustrator. Born in 1914 as Jacob Ovcharov in Kiev, Ukraine. Immigrated to the U.S. in 1922. Died in 1997 in Puerto Rico where he had lived since 1946.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Kenny, Elizabeth, -- 1886-1952.; United States. -- Farm Security Administration; United States. -- Office of War Information; Archives of American Art; Acadians -- Maine; Depressions -- 1929.; Farmers -- Maine; Photography; Railroads -- West (U.S.); Maine -- Description and travel; Puerto Rico -- Description and travel; Southern States -- Description and travel; Virgin Islands -- Description and travel; West (U.S.) -- Description and travel; Composers; Illustrators; Motion picture producers; Photographers